2014
DOI: 10.1002/hipo.22397
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity daily walking activity is associated with hippocampal volume in older adults

Abstract: Hippocampal atrophy is associated with memory impairment and dementia and serves as a key biomarker in the preclinical stages of Alzheimer's disease. Physical activity, one of the most promising behavioral interventions to prevent or delay cognitive decline, has been shown to be associated with hippocampal volume; specifically increased aerobic activity and fitness may have a positive effect on the size of the hippocampus. The majority of older adults, however, are sedentary and have difficulty initiating and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
112
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 87 publications
12
112
4
1
Order By: Relevance
“…This finding is consistent with a recent study that reported positive associations between steps per day (i.e., physical activity) and hippocampal volume in women but not men (Varma et al., 2015). Other randomized control trials have also found evidence for gender‐specific effects (van Uffelen, Chinapaw, van Mechelen, & Hopman‐Rock,2008; Vaughan, Morris, Shum, O'Dwyer, & Polit, 2012), with data suggesting the superior cognitive response in women may be the result of gender differences in exercise‐induced hormonal glucometabolic and hypothalamic–pituitary–adrenal axis responses (Baker et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is consistent with a recent study that reported positive associations between steps per day (i.e., physical activity) and hippocampal volume in women but not men (Varma et al., 2015). Other randomized control trials have also found evidence for gender‐specific effects (van Uffelen, Chinapaw, van Mechelen, & Hopman‐Rock,2008; Vaughan, Morris, Shum, O'Dwyer, & Polit, 2012), with data suggesting the superior cognitive response in women may be the result of gender differences in exercise‐induced hormonal glucometabolic and hypothalamic–pituitary–adrenal axis responses (Baker et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In older adults, large‐scale cross‐sectional studies have reported contradictory associations. Positive associations between CRF/physical activity and RAVLT performance have been reported (Boots et al., 2014; Pizzie et al., 2014; Zhu et al., 2014) while others studies did not observe such associations (Maass et al., 2015; Varma et al., 2015). Randomized controlled trials provide evidence that aerobic exercise (Klusmann et al., 2010) and resistance exercise (Cassilhas et al., 2007) training can improve episodic memory in cognitively healthy older adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of greater brain volume in temporal brain regions in physical active older adults in comparison with less active older adults can be found as well [8]. Increasing amount of research suggests increase of volume in hippocampus and reduced brain atrophy due to physical exercise [7,9].…”
Section: Introductionmentioning
confidence: 98%